Quantitative evaluation of China's adolescent physical activity policies: a PMC Index model approach - Huang, Xinzhu; Zhang, Changsheng; Li, Jiang; Ding, Xianming (Frontiers in Public Health, 2025)
BackgroundChina has promulgated a series of policies to address the health crisis among adolescents resulting from physical inactivity. These policies aim to promote physical activity among Chinese Adolescent and improving health. As institutional mechanisms for building social consensus and providing strategic guidance, evaluating and optimizing these policies to enhance their efficacy represents a critical imperative.MethodThis paper employs the PMC-Index model to conduct text mining on 9 adolescent Physical fitness policies implemented in China since the inception of the new century. This paper first constructs PMC-Index model, then conducts quantitative analysis on the text, and finally calculates the scores of nine policies in various dimensions to analyze the advantages and disadvantages of the policies. In addition, this paper performs visual analysis by drawing a curved surface diagram.ResultThe nine adolescent sports health promotion policies in China yield an average score of 6.83, indicating a generally sound status overall. However, deficiencies exist in supervising policy implementation, coordinating stakeholder responsibilities, and ensuring policy safeguards.ConclusionsThe results indicate that China should strengthen the application of youth sports supply-side policy instruments in the future, clarify the division of responsibilities among schools, families and communities, improve the reward and punishment mechanism of policy implementation, and effectively improve the effectiveness of youth Physical fitness policies.